Isolasi dan Karakterisasi Agarosa dari Rumput Laut Gracilaria verrucosa - ZAINAL ABIDIN; MARCELLINO RUDYANTO; SUDJARWO SUDJARWO (Fakultas Farmasi Universitas Pancasila, 2015)
: Agar is complex polysaccharide which could be isolated from group Rhodophyta of seaweeds, sucs as Gracilaria verrucosa. Agar consists of two components, namely agarose and agaropectin. Agarose is neutral polysaccharide, while agaropectin is polysaccharide that contain sulphate, so agarose could be used for gel electrophoresis. The use of NaOH solution was aimed to hydrolyzes the agar to form 3,6-anhydro-L-galactose, whereas the use of propylene glycol was to separates agarose from agaropectin. This research was aimed to isolate agarosa from Gracilaria verrucosa using NaOH solution with the concentrations of 4%, 6%, 8%, 10% and propylene glycol of 30, 50 and 70 mL. The agarose obtained was giving specivic absorbtion band in IR spectrum with wave number in the region of 930 and 890 cm-1, and there were absorbtion band in the region of 860 and 830 cm-1, indicated that the agarose still contained sulphate. The increase of NaOH concentration and propylene glycol volume caused drawback sulphate and ash content, constant melted temperature and gel temperature but increase gel strength. The best amount of agarose was obtained with the use of NaOH 10% and 70 mL of propylene glycol, with the characteristics were: ash content of 2.0035±0.0429% (w/w), sulphate content of 0.3236±0.0131% (w/w), melted temperature of 34 oC, gel temperature of 90 oC, gel strength of 432.195±26.172 g/cm2 and degree of electroendosmosis of 0.20±0.005.